(untitled) (Филологические заметки, 2019)
The article focuses on Slovenian literary characters from the narrative works of the second half of the 20th century, which are said to stem from German tradition. Particular attention is being paid to the analysis of the portrait, role and status of these characters as well as to the detection of ascendant reception patterns of Germans and things German in Slovenian narrative of the 19th century.